Specialised dictionaries for learners - Fuertes Olivera, Pedro Antonio (Lexicographica. Series maior, 2010)
This book defends two main ideas: there is a need and a market for better specialised dictionaries for learners; we need a sound theoretical framework for coping with known and unknown challenges (for example the Internet) in the realm of pedagogical specialised lexicography. Both themes were Enrique Alcaraz's driving force during his life. Hence, his memory deserves this book that has been written by leading scholars in the field - they have compiled more than 70 dictionaries and published hundreds of books and articles on the topics here discussed - although only two of them knew him in pers.